2016
DOI: 10.1089/rej.2015.1710
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dynapenia, Sarcopenia, and Cognitive Impairment Among Community-Dwelling Older Taiwanese

Abstract: A decline in physical and/or cognitive function is a common feature of aging, and frailty has been shown to be associated with cognitive impairment and dementia. This study aimed to evaluate the association between dynapenia, sarcopenia, and cognitive impairment among community-dwelling older people in Taiwan. Data from the I-Lan Longitudinal Aging Study (ILAS) were retrieved for study. Global cognitive function was assessed by Mini-Mental State Examination (MMSE), whereas the Chinese Version Verbal Learning T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 37 publications
8
74
2
2
Order By: Relevance
“…The present study is the first investigation that confirmed the association of physical activity and cognitive dysfunction in the middle-aged and older Korean populations. The results of our study are consistent with previous reports showing that physical activity is associated with risk of cognitive dysfunction and mild cognitive impairment [16][17][18][19]. For example, a study on the community-dwelling older adults reported that daily physical activity was associated with cognitive function variability in the elderly [20].…”
Section: Discussionsupporting
confidence: 92%
“…The present study is the first investigation that confirmed the association of physical activity and cognitive dysfunction in the middle-aged and older Korean populations. The results of our study are consistent with previous reports showing that physical activity is associated with risk of cognitive dysfunction and mild cognitive impairment [16][17][18][19]. For example, a study on the community-dwelling older adults reported that daily physical activity was associated with cognitive function variability in the elderly [20].…”
Section: Discussionsupporting
confidence: 92%
“…For example, one study tracked these conditions’ association with falls in 674 community-dwelling older individuals [24], and another examined associations with cognitive functional disorders for older community-dwellers in Taiwan [25]. Yet another study investigated risk factors for mortality in 1149 older people in Brazil [16].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, Huang et al . discovered that slowness and weakness with non-muscle etiology were strongly associated with cognitive impairment21. In addition, Wu et al .…”
Section: Discussionmentioning
confidence: 99%